1996
DOI: 10.1161/01.cir.93.7.1364
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Variation of Ambulatory Myocardial Ischemia

Abstract: Exogenous factors (physical and mental activities) are most potent as triggers of ischemia during the morning hours, and the postural change after awakening contributes to the morning increase in ischemia. There is also evidence for an endogenous, activity-independent circadian influence on ischemic susceptibility that is independent of exogenous factors and that sustains the increase in ischemia upon awakening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(22 citation statements)
references
References 42 publications
2
19
0
1
Order By: Relevance
“…In some patients orthostatic hypertension is another possibility [46]. Our finding is compatible with the results of other studies which have demonstrated that postural changes on awakening may trigger myocardial ischemia [47]. …”
Section: Discussionsupporting
confidence: 92%
“…In some patients orthostatic hypertension is another possibility [46]. Our finding is compatible with the results of other studies which have demonstrated that postural changes on awakening may trigger myocardial ischemia [47]. …”
Section: Discussionsupporting
confidence: 92%
“…For instance, myocardial ischemia during daily life shows a characteristic circadian rhythm. 219 Even though exogenous factors (ie, the amount of physical and mental activity) trigger episodes of myocardial ischemia, 208,209,219 Krantz et al 219 demonstrated that the circadian rhythm of myocardial ischemia also appears to have an endogenous component, as demonstrated in Figure 7. Understanding the factors driving this apparent endogenous component could help further elucidate the pathophysiology of mental stress-induced ischemia.…”
Section: Induction Of Myocardial Ischemiamentioning
confidence: 99%
“…We also showed that 458 nm light exposure caused a lower DSBP and DDBP compared with exposure to 550 nm light, which might be associated with the color effect of 458 nm light. Previous studies showed that the risk of myocardial infarction, stroke, and sudden death shows a peak in the early morning (Marler et al, 1989;Muller et al, 1989;Kranz et al, 1996), and the morning shift in cardiac sympatho-vagal balance may be involved in this increased risk of cardiovascular incidents at that time (Furlan et al, 1990;Esler, 2000). The relaxing effect of 458 nm light might be useful in the avoidance of such incidents.…”
Section: Discussionmentioning
confidence: 99%